2010
DOI: 10.3390/md8102578
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Investigations of American Oysters Using 1H-NMR Spectroscopy

Abstract: The Eastern oyster (Crassostrea virginica) is a useful, robust model marine organism for tissue metabolism studies. Its relatively few organs are easily delineated and there is sufficient understanding of their functions based on classical assays to support interpretation of advanced spectroscopic approaches. Here we apply high-resolution proton nuclear magnetic resonance (1H NMR)-based metabolomic analysis to C. virginica to investigate the differences in the metabolic profile of different organ groups, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 59 publications
1
75
1
Order By: Relevance
“…This procedure yielded specific metabolic profiles visualizing possible changes in the osmolyte composition of D. lineata and their relative concentrations caused by salinity alterations. Specific metabolites were identified using the Chenomx Software database and chemical shift tables (Tikunov et al 2010). Osmolyte signals of interest were analysed in more detail.…”
Section: Cellular Responsementioning
confidence: 99%
“…This procedure yielded specific metabolic profiles visualizing possible changes in the osmolyte composition of D. lineata and their relative concentrations caused by salinity alterations. Specific metabolites were identified using the Chenomx Software database and chemical shift tables (Tikunov et al 2010). Osmolyte signals of interest were analysed in more detail.…”
Section: Cellular Responsementioning
confidence: 99%
“…High resolution proton nuclear magnetic resonance (HR-1 H NMR) spectroscopy is particularly suitable for the measurement of a large number of metabolites in biological samples because it is rapid, non-invasive and is rich in structural and quantitative information (Brindle et al, 2002;Lindon et al, 2000). NMRbased metabolomics has been effi ciently used in several recent studies in marine environmental toxicology (Viant et al, 2001;Viant et al, 2006aViant et al, , 2006bJones et al, 2008;Williams et al, 2009;Gordon and Leggat, 2010;Lannig et al, 2010;Santos et al, 2010;Tikunov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2,14 In a previous 1 H NMR metabolomic study, we have shown that betaine was the most abundant metabolite in all oyster tissues. 9 Betaine is an important metabolite functioning both as an osmolyte to protect against osmotic stress and a methyl group donor. 9,15 Hence, glucose was chosen to probe glycolysis and the Krebs cycle, while glycine was chosen to probe betaine, which is trimethylglycine, a catabolic product of glycine.…”
Section: Introductionmentioning
confidence: 99%
“…9 Betaine is an important metabolite functioning both as an osmolyte to protect against osmotic stress and a methyl group donor. 9,15 Hence, glucose was chosen to probe glycolysis and the Krebs cycle, while glycine was chosen to probe betaine, which is trimethylglycine, a catabolic product of glycine. 14 Therefore, the major goal of this study was to establish baseline distributions of metabolites derived from U-13 C-glucose and 2-13 C-glycine over oyster tissues by using 13 C NMR measurement and to demonstrate the feasibility of using NMR for that purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation